Systematic analysis of the interaction mechanism between platelets and coronary heart disease: from molecular pathways to new strategies for plant based antiplatelet therapy - Liao, Li; Li, Xiaoxuan; Xu, Hong; Tang, Jing; Li, Bo; Tang, Yan; Xie, Fang (Frontiers in Pharmacology, 2025)
Coronary Heart Disease (CHD) stands as a predominant cardiovascular ailment globally, posing a severe menace to human health. Central to both hemostasis and the pathogenesis of coronary atherosclerotic thrombosis are platelets. In recent years, their significance has expanded beyond mere involvement in clot formation; they have been implicated in heightened immune responses, contributing to tissue inflammation (evident in myocardial ischemia) and vascular inflammation (crucial in vulnerable plaque formation). While contemporary antiplatelet therapies have markedly enhanced clinical outcomes for patients with coronary artery disease, they inadvertently escalate the hazard of bleeding complications. This review delves into the intricate mechanisms by which platelets influence the progression of coronary artery disease and meticulously examines the prospective utility of herbal antiplatelet interventions. Our objective is twofold: firstly, to furnish clinicians with scientifically grounded and valuable therapeutic alternatives for managing coronary artery disease, and secondly, to stimulate research and development endeavors aimed at creating novel, more efficacious antiplatelet medications that strike a balance between efficacy and safety.